The Relationship Between the Need for Learning Materials and Interest of the Participants of the Majelis Taklim Syuhada’ Fisabilillah - Sandra Novelisa; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low interest of participants in the Taklim Syuhada' Fisabilillah Council of Pesisir Selatan Regency. This study aims to 1) describe the learning material needs of the participants of theFisabilillahTaklim Martyrs' Council of Peisisir Selatan Regency, 2) describe the learning interest of the participants of the Taklim Martyrs' Council of Fisabilillah, Peisisir Selatan Regency, and 3) find out the relationship between the needs of learning materials and the interests of the participants of the Taklim Syuhada Council participants. ' Fisabillah Pesisir Selatan Regency. This research includes correlational quantitative research. The population in this study was 60 people. The number of samples in this study was 30 people. The simple random sampling technique was taken as many as 50% of the participants. The data collection technique used is a questionnaire, while the data collection tool uses a questionnaire containing a list of statements. Data analysis technique using percentage and product moment. From the results of the study, it can be seen that (1) the learning material needs of the participants of the Taklim Syuhada' Fisabilillah Council of Peisisisir Selatan Regency are categorized as low, (2) the learning interest of the participants of the Majelis Taklim Syuhada' Fisabilillah of Peisisisir Selatan Regency is categorized as low, and (3) there is a significant relationship between the needs of learning materials with the interest of participants in the Taklim Martyrs' Council of Fisabilillah, Peisisir Selatan Regency.